Algas epífitas de Bajo Pepito, Isla Mujeres, Quintana Roo, México - Quan-Yong, L. I.; Díaz-Martín, M. A.; Espinoza-Avalos, J. (Revista de Biología Tropical, 2006)
A total of 96 epiphytic algae species were identified from Bajo Pepito, Quintana Roo, México. 60.4% (58) belonged to the Rhodophyta, 19.79% (19) to the Phaeophyta, 16.6% (16) to the Chlorophyta and 3.1% (3) to the Cyanophyta; 49 species (50.5%) were found only in one month, while Heterosiphonia crispella was found in all of the sampled months. That species provided the largest contribution to the biomass of epiphytes. During January we registered the greater biommass and richness of epiphytes species, coincidently with high values of host species cover and rainfall.